PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Lu, Cheng-Peng; Wei, Chao-Guang; Zhu, Jun-Quan; Tang, Dao-Jun; Wang, Chun-Lin; Hou, Cong-Cong (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the full-length sequence of PtP38 gene was cloned from Portunus trituberculatus and its structure was analyzed by bioinformatics methods. To study the function of PtP38 gene after Gram-negative bacteria infection, we injected P. trituberculatus with LPS to active the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, the activities of antioxidant enzymes (superoxide dismutase (SOD), catalase (CAT) and inducible nitric oxide synthase (iNOS) enzymes), and the expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conformed the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes and promoting cell apoptosis in infected P. trituberculatus. This study also laid the foundation for further study of the P38 MAPK signaling pathway and the immune mechanism of P. trituberculatus.